THE EFFICACY OF CHITOSAN FROM WINDU SHRIMP SHELLS AS A PRESERVATIVE OF FRESH KENYAR FISH IN THE FORM OF DARNE DURING STORAGE AT ROOM TEMPERATURE - Ni Nyoman Rupiasih; Yosefa Yakunda Tandu; Nyoman Wendri; S. S. Jagtap (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2022)
This study is about the efficacy of chitosan from windu shrimp shells (Panaeus monodon) as a preservative for fresh fish in the form of darne (steak), namely fresh kenyar fish (Sarda orientalis) during storage at room temperature. The chitosan solution used are chitosan solution with concentration of 1%, 1.5%, 2%, and 2.5%. The fish samples which soaked in that solutions are named T1, T2, T3, and T4, respectively .. The soaking time were 20, 40 and 60 minutes. As control were fish without treatment (C-0) and fish soaked in acetic acid (C-A). All samples stored at room temperature. The activity of chitosan as fish preservative was analyzed through pH and antimicrobial test. The pH test were made in the range of 0, 24, 48 and 72 h. The antimicrobial test was done on the storage period 24 h. The results showed that the greater the concentration of chitosan solution, the shorter the soaking time required to obtain the benefits of chitosan as an antimicrobial agent for fish preservation, especially kenyar fish in the form of darne. The fish that are still suitable for consumption for 24 hours of storage are fish that are soaked in a 2.5% (T4) chitosan solution at either 20, 40, or 60 minutes of soaking time.